2010
DOI: 10.1002/jso.21511
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐operative contrast‐enhanced ultrasound improves image enhancement in the evaluation of liver tumors

Abstract: Contrast-enhanced ultrasound is safe and effective in pre-resection and pre-ablation treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…According to the concept of a parenchymal‐sparing resection in a patient with CRLM, we preferred to do a conversion and thus avoid a larger resection. To solve the problems related to a better definition of tumoural lesions, intra‐operative contrast‐enhanced ultrasound could be useful in assessing not only tumour margins but also in visualizing missing lesions . Although such software has shown that it is possible to make it easier to define intra‐operatively the position of the tumour through the laparoscopic view, the absence of a real‐time 3‐D identification forces us to use the major portal pedicles or hepatic veins as the only landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…According to the concept of a parenchymal‐sparing resection in a patient with CRLM, we preferred to do a conversion and thus avoid a larger resection. To solve the problems related to a better definition of tumoural lesions, intra‐operative contrast‐enhanced ultrasound could be useful in assessing not only tumour margins but also in visualizing missing lesions . Although such software has shown that it is possible to make it easier to define intra‐operatively the position of the tumour through the laparoscopic view, the absence of a real‐time 3‐D identification forces us to use the major portal pedicles or hepatic veins as the only landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…3 This is particularly true for small lesions where the US sensitivity is even lower than in larger lesions or for those lesions with insufficient echogenic contrast compared to surrounding tissues. [4][5][6][7] However, the radiological evaluation of ablated tissues poses serious limitations to cross-sectional imaging especially regarding the postoperative differentiation of tumor recurrences from the normal scarring process. Recurrences are usually present as a rim of contrast uptake peripheral to the ablated area 8,9 in the transitional ischemic zone that surrounds the core ablated zone [10][11][12][13] and where the scarring process also takes place normally.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low sensitivity (40–77%) and specificity progressively limited its applications favoring over time cross‐sectional imaging modalities (computed tomography [CT] and magnetic resonance imaging [MRI]) . This is particularly true for small lesions where the US sensitivity is even lower than in larger lesions or for those lesions with insufficient echogenic contrast compared to surrounding tissues . However, the radiological evaluation of ablated tissues poses serious limitations to cross‐sectional imaging especially regarding the postoperative differentiation of tumor recurrences from the normal scarring process.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, little is known about the addition of CEUS for renal imaging in the intraoperative setting. Intraoperative CEUS (IO‐CEUS) has been used in liver imaging, demonstrating improved lesion detection and characterization compared with CT or MRI . At our institution, it is standard procedure to perform an intraoperative ultrasound during open partial nephrectomy to evaluate the extent of tumor involvement and detect additional unexpected lesions, thereby guiding surgical intervention.…”
mentioning
confidence: 99%
“…Intraoperative CEUS (IO-CEUS) has been used in liver imaging, demonstrating improved lesion detection and characterization compared with CT or MRI. 5,6 At our institution, it is standard procedure to perform an intraoperative ultrasound during open partial nephrectomy to evaluate the extent of tumor involvement and detect additional unexpected lesions, thereby guiding surgical intervention. We hypothesize that the addition of IO-CEUS would improve lesion detection and characterization, and thus potentially alter surgical management.…”
mentioning
confidence: 99%